Influence of Pr doping on the thermal, structural and optical properties of novel SLS-ZnO glasses for red phosphor - Mohamed, Nurzilla; Hassan, Jumiah; Matori, Khamirul Amin; Azis, Raba'ah Syahidah; Abdul Wahab, Zaidan; Mohd Ismail, Zamratul Maisarah; Baharuddin Pallan, Nur Fadilah; Abdul Rashid, Siti Syuhaida (Elsevier, 2017)
A novel environmental friendly strategy towards red phosphors in optoelectronic applications employing Pr6O11 doped SLS-ZnO with chemical composition x(Pr6O11)·100-x(SLS·ZnO) where x = 0, 1, 2, 3, 4 and 5 wt% via melt-quenching technique was successfully synthesized. The X-ray Diffraction (XRD) patterns of all these glasses show broad and diffused humps, which confirm the amorphous structure of samples. The Differential Thermal Calorimetry (DSC) indicated that the value of glass transition is higher from 625 °C to 637 °C with increasingly of Pr6O11 content. Fourier Transform Infrared Spectra (FTIR) spectra display a decreasing trend towards a smaller wavenumber with the increase of Pr content is due to the formation of non-bridging oxygen (NBO) in SLS-ZnO host matrix. The absorption spectra had revealed the most intense absorption band at ∼444 nm, which was assigned as excitation wavelength to determine the photoluminescence (PL) emission intensity of the glass. The indirect band gap values varies from ∼2.44 eV to ∼3.02 eV as a function of Pr6O11 concentration. The PL emission bands at ∼530 (blue), ∼556 (green), ∼613 (red) and ∼650 (red) nm increases from 0 wt% to 4 wt% and slightly decreases as Pr6O11 increases with a maximum at 5 wt%. Therefore, the SLS-ZnO doped with Pr6O11 as a good potential as red phosphors in an optoelectronic application in accordance with the highest red emission intensity at ∼613 nm and ∼650 nm.